2021
DOI: 10.1038/s41467-021-22431-6
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin in the ventromedial hypothalamus regulates peripheral glucose metabolism

Abstract: The hypothalamus plays a central role in monitoring and regulating systemic glucose metabolism. The brain is enriched with phospholipids containing poly-unsaturated fatty acids, which are biologically active in physiological regulation. Here, we show that intraperitoneal glucose injection induces changes in hypothalamic distribution and amounts of phospholipids, especially arachidonic-acid-containing phospholipids, that are then metabolized to produce prostaglandins. Knockdown of cytosolic phospholipase A2 (cP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Apart from the different hyperglycemic mice models, the direct administration of glucose into the mouse third ventricle has shown a significant increase in the nuclear factor kappa light chain enhancer of activated B cells (NF-κB) activity in the hypothalamus [20]. In line with this, other studies reported that direct intraperitoneal injection of glucose in rodents also increased hypothalamic Il-1α, Il-1β mRNA and prostaglandins (PG) level [3,88]. Additionally, in vitro studies have shown that primary cultures of microglia, astrocytes, or Muller glial cells exposed to high glucose conditions exhibited increased production of inflammatory cytokines and reactive oxygen species (ROS) via activation of inflammatory signaling pathways [28,[89][90][91].…”
Section: B Hyperglycemiamentioning
confidence: 81%
See 1 more Smart Citation
“…Apart from the different hyperglycemic mice models, the direct administration of glucose into the mouse third ventricle has shown a significant increase in the nuclear factor kappa light chain enhancer of activated B cells (NF-κB) activity in the hypothalamus [20]. In line with this, other studies reported that direct intraperitoneal injection of glucose in rodents also increased hypothalamic Il-1α, Il-1β mRNA and prostaglandins (PG) level [3,88]. Additionally, in vitro studies have shown that primary cultures of microglia, astrocytes, or Muller glial cells exposed to high glucose conditions exhibited increased production of inflammatory cytokines and reactive oxygen species (ROS) via activation of inflammatory signaling pathways [28,[89][90][91].…”
Section: B Hyperglycemiamentioning
confidence: 81%
“…Additionally, it employs an integrated neuroendocrine network to direct peripheral metabolic activities. Through these mechanisms, the hypothalamus acts as a metabolic center that controls a variety of functions, such as glucose and fat metabolism [3,4], nutrient sensing [5], food intake behavior [6], body temperature regulation [7], energy homeostasis [8], blood pressure (BP) regulation [9], and aging [10]. At the cellular level, these physiological functions are conducted by several groups of neurons located in the mediobasal hypothalamus (MBH), paraventricular nucleus (PVN), and lateral hypothalamus (LH), which regulate the controlled synthesis, release, and action of hypothalamic neuropeptides and neurotransmitters [11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported an increase in PGE2 levels in the arcuate nucleus following high fat diet (HFD) feeding [9]. Interestingly, we found a near-significant increase in expression of the receptor EP4 (encoded by the gene, Ptger4) in isolated microglia but not whole hypothalamus from HFD-fed mice (Supplementary Fig.…”
Section: Microglial Ep4 Deletion Reduced Susceptibility To Diomentioning
confidence: 66%
“…A recent study implicated hypothalamic PGE2 in microglial activation and metabolic regulation during DIO [9]. Preventing the increase in ventromedial hypothalamic PGE2 during HFD feeding by targeted knock-down of an enzyme involved in the generation of prostaglandin precursor molecules reversed microgliosis and improved glucose tolerance on HFD [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation